PENERAPAN PEMBELAJARAN KOLABORATIF PADA MATA PELAJARAN MATEMATIKA DI SMKN 1 KOTABUMI - Ratih Handayani; Eka Wiwik Sulistiawati (Universitas Muhammadiyah Kotabumi, 2019)
The application of Collaborative Learning in mathematics subjects is a problem in this study. The purpose of this study was to find out how to apply collaborative learning in mathematics subjects at Kotabumi 1 Vocational School. The method used in this research is qualitative descriptive. The implementation of collaborative learning is carried out in the aspects of learning tools, teaching materials, learning media, and the implementation of learning. The implementation of learning in the classroom is carried out in 8 meetings Students who are the subject of research are students of class XI TKJ 1. Based on observations it can be concluded that the application of Collaborative learning can improve the quality of lecturers, teachers, and students to learn from each other in subjects.